What Are the Benefits of Hip Resurfacing in Appropriate Patients? A Retrospective, Propensity Score-Matched Analysis. Issue 2 (December 2020) - McLawhorn, Alexander S.; Buller, Leonard T.; Blevins, Jason L.; Lee, Yuo Yu; Su, Edwin P.
Background: Hip arthritis is one of the major causes of disability worldwide. Hip resurfacing arthroplasty (HRA) has emerged in recent years as an alternative to total hip arthroplasty (THA), but complications of HRA have limited the patient population to younger male patients with primary osteoarthritis and large hip anatomy. How the functional benefits of HRA in this population compare with those of THA is not entirely clear. Questions/Purposes: The primary aim of this study was to determine whether there were differences in hip disability and patient satisfaction with surgery between these two groups at 2 years after surgery, using patient-reported outcome measures (PROMs) and subjective measures of patient satisfaction. Additionally, we sought to determine whether there were differences in post-operative discharge disposition, revision rates, or adverse events. Methods: We searched an institutional database to identify patients undergoing unilateral HRA or THA between January 2007 and July 2011 who met today's recommended criteria for HRA: younger male patients with large-enough hip anatomy to make surgery viable (a femoral head of at least 48 mm in HRA patients and, in THA patients, an acetabular shell size of 54 mm, the minimum outer shell size that could accommodate a femoral head component of 48 mm; for matching purposes, acetabular shell size in THA was used as a surrogate for the femoral head size used in HRA). We used propensity score matching to control for potentially confounding pre-operative variables and administered the Hip Disability and Osteoarthritis Outcome Score (HOOS) survey, including its subdomains, at the 2-year mark. We also assessed differences between groups in Lower Extremity Activity Scale scores, 12-item Short Form Health Survey results, and answers regarding satisfaction with surgery. We calculated minimal detectable change, minimum clinically important change, and substantial clinical benefit using anchor-based techniques for multiple outcome measures. Results: There were 251 patients in each group. HRA patients scored significantly higher than THA patients on the 2-year HOOS sports and recreation (92 versus 87, respectively) and on rates of overall satisfaction (94% versus 89%, respectively). The HRA group also had a greater chance of achieving minimum clinically important change (18.75 points) in the HOOS sports and recreation subdomains than the THA group (97% versus 91%). No significant difference was found in 6-month adverse event rates. HRA patients also had a significantly shorter mean hospital stay, a higher rate of discharge to home, and a lower incidence of a "significant" limp after surgery. Conclusion: HRA may provide a functional benefit in sports and recreation and greater satisfaction in patients who meet the current criteria for HRA. Because these benefits may be small, pre-operative counseling should focus on balancing the possible functional benefits against the longer-term risks associated with metal-on-metal bearings.